Digital Audio Visual Pop Up Book Media in the Civics Subject for Grade IV Elementary School Students Muhammadiyah 11 Medan - Darnia Darnia (Berpusi Publishing, 2025)
This research is motivated by the limited availability of digital media for elementary school students. In the ever-evolving digital era, the use of technology-based learning media is very important as a solution to increase learning effectiveness. This research is a development research that produces a product media in the form of a digital audio-visual pop-up book. This study aims to determine the steps for developing a digital audio-visual pop-up book media in the Civics Phase B subject at Muhammadiyah 11 Elementary School, Medan, East Medan. The type of research used is development research (Research and Development ) using the ADDIE model, namely analyze, design, development, implementation, and evaluation. The subjects of this study were fourth-grade students of Muhammadiyah 11 Elementary School, Medan. The object of this research is a digital audio-visual Pop-Up Book media with power point and capcut applications to facilitate and motivate learning abilities in Civics subjects. Data collection techniques are observation, expert validation, and questionnaires. Expert validation is media, language and material validation. The trial design is given to validators and users. The results of the development of Audio Visual Pop Up Book Media by expert validators are material experts 82% in the